PETROLEUM CHARGE AND MIGRATION IN THE BLACK SEA: INSIGHTS FROM OIL AND SOURCE ROCK GEOCHEMISTRY. (15th June 2018) - Mayer, J.; Sachsenhofer, R.F.; Ungureanu, C.; Bechtel, A.; Gratzer, R.; Sweda, M.; Tari, G.
Abstract : Although a number of significant oil and gas discoveries have been made within the Western Black Sea and the surrounding area, only sparse data about migration mechanisms are available. In this paper, biomarker and isotope data from five oilfields and one oil show located offshore Bulgaria and Romania (in the western Black Sea), and from one field onshore Georgia (at the margin of the eastern Black Sea), were compared with geochemical data from potential source rock intervals from borehole samples. The source rock data came from offshore Bulgaria and outcrop samples from onshore Georgia. The biomarker data indicates that all the oils analysed were generated by source rocks of Late Cretaceous or Cenozoic age. In the Western Black Sea sub‐basin, the most likely source rocks are Oligocene to Lower Miocene shales of the Maikop Group. Compound‐specific isotope data indicate that Lower Oligocene source rocks are the most significant although a contribution by Lower Miocene diatom‐rich source rocks cannot be excluded. For an oil sample from the Shromisubani field onshore Georgia, isotope data from individual n‐alkanes together with biomarker data indicates that the oil contains a mixture of hydrocarbons generated from the Middle Eocene Kuma Formation and the Oligocene part of the Maikop Group. Oligocene and Miocene source rocks are immature at the shelfal locations where the oil samples were recovered. Charge for these hydrocarbon accumulations is interpreted to have been provided by long‐distance lateral migration from source kitchens in more central parts of the Black Sea basin, where Oligocene and (some) Miocene source rocks are within the oil and gas window. The results of this study highlight the prospectivity of recently‐discovered deep‐water plays, and significantly de‐risk future deep‐water projects within the Black Sea area.